Optimisation of fuel in fire tube saturated steam boiler. (13th August 2019) - Ibrahim, Uzair; Farrukh, Sarah; Hussain, Arshad; Niazi, Muhammad Bilal Khan
Considerable improvements have been made to minimise the fuel consumption in industrial boilers since a sizable portion of the operational cost can be reduced with fuel optimisation. In this study a combination of air preheater and condensing economiser is proposed to optimise the fuel usage in a fire tube heat boiler. The process utilises 10% excess air that is preheated to 96°C in an air preheater using the heat of stack flue gases. This improves the boilers efficiency by 3%. Moreover, makeup water is also heated to 84°C in the condensing economiser using the heat of stack flue gases coming from the air preheater. This proposed assembly extracts most of the energy from stack flue gases before it start to condense. A simulation using ASPEN HYSYS® shows that using preheated make up water and preheated combustion air, fuel demand in the boiler is reduced by 10%, thus making the process more economical.